Self-Reported Dental Public Health Competencies of Senior Dental Students: A Cross-Sectional Study - Shahbazi, Soheil; Khoshnevisan, Mohammad Hossein; Malekmohammadi, Mahsa; Ghorbani, Zahra (Journal of Dental School, 2021)
Objective: To reach the World Health Organization’s goal of improving community oral health, Iranian oral health policy-makers expanded the scope of oral health by including dental public health (DPH) courses in the latest dental curriculum to improve students’ competencies. The aim of the current study was to evaluate DPH competencies in senior dental students at Shahid Beheshti University of Medical Sciences, according to specified educational objectives. Methods: In the present cross-sectional study, 195 senior dental students (enrolled in 2014-2015) filled up an online standardized questionnaire. The instrument included demographic information as well as 31 statements about ten domains of DPH. Participants used self-assessment method to report the level of their competencies on a Likert scale of 0-10; Zero indicating "not competent at all", and 10 indicating "fully competent" for each statement. Then the mean score was calculated for each domain. Data analysis was conducted using Independent samples, T-test, One-way ANOVA, Mann-Whitney U-test, and Kruskal-Wallis via SPSS version 21. ResultsThe sum of scores for each participant was within the range of 63 to 310, and the mean (SD) was 216.68 (±43.69). Students were most competent in "Providing preventive dental care" (8.22±1.59), "Adherence to professional ethics" (7.56±1.68), and" Understanding determinants of oral health" (7.50±1.52). They were least competent in "Understanding components and functions of healthcare system" (5.96±2.06), "Planning" (6.06±2.45), and "Oral health research" (6.24±2.44). The mean score for females’ (223.30±38.21) was significantly higher than males’ score (207.15±49.25), (P=0.011). Conclusion: Although higher competencies were achieved in "Providing preventive dental care", "Adherence to professional ethics", and" Understanding determinants of oral health"; there are more areas to be accomplished, such as "Understanding components and functions of healthcare system", "Planning", and "Oral health research". These findings could be helpful either in revising the content materials, teaching methods, or both.